Feedback control of Set1 protein levels is important for proper H3K4 methylation patterns - Soares, Luis M. (2014)
Methylation of histone H3 lysine 4 by the Set1 subunit of COMPASS correlates with active transcription. Here we show that Set1 levels are regulated by protein degradation in response to multiple signals. Set1 levels are greatly reduced when COMPASS recruitment to genes, H3K4 methylation, or transcription is blocked. The degradation sequences map to N-terminal regions that overlap a previously identified auto-inhibitory domain, as well as the catalytic domain. Truncation mutants of Set1 that cause under- or over-expression produce abnormal H3K4 methylation patterns on transcribed genes. Surprisingly, SAGA-dependent genes are more strongly affected than TFIID-dependent genes, reflecting differences in their chromatin dynamics. We propose that careful tuning of Set1 levels by regulated degradation is critical for establishment and maintenance of proper H3K4 methylation patterns.